Promoting organ donation in Russia: problems and prospects - G. N. Komkova; E. N. Toguzaeva; A. V. Basova; M. S. Karamysheva (Вестник трансплантологии и искусственных органов, 2025)
Transplantation helps to save the lives of patients with end-stage diseases of the liver, heart, lungs, and kidney.Objective: to study the strategies for advancing the idea of organ donation in the Russian Federation.Materials and methods. Scholarly publications by Russian researchers on the issue at hand. The study’s methodology was based on application of general and specific scientific methods of theoretical analysis.Results. An assessment of how opportunities were used to legitimately promote the idea of donation was conducted.Conclusion. Modern ways and methods of promoting the idea of organ donation will help to introduce into public attention the importance of organ donation for transplantation.